2012
DOI: 10.1016/j.febslet.2012.06.025
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 repressed USP7 expression is crucial for colon cancer development

Abstract: Edited by Varda Rotter Keywords:Colon cancer STAT3 USP7 P53 a b s t r a c t Interleukin-6 (IL-6) induced STAT3 activation is viewed as crucial for multiple tumor growth and metastasis, including colon cancer. However, the molecular mechanisms remain largely unexplored. Here, we show that expression of ubiquitin-specific protease 7 (USP7), a deubiquitylating enzyme, is decreased in STAT3-positive tumors. IL-6 administration or transfection of a constitutively activated STAT3 in SW480 cells also repressed USP mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Our data are in accordance with a recent study by Yang et al (2012) that reports that, in colon tumors, IL-6 can inhibit USP7 expression in a STAT3-dependent manner. Furthermore, we show that the association of USP7 and Foxp3 is disrupted upon short-term IL-6 stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…Our data are in accordance with a recent study by Yang et al (2012) that reports that, in colon tumors, IL-6 can inhibit USP7 expression in a STAT3-dependent manner. Furthermore, we show that the association of USP7 and Foxp3 is disrupted upon short-term IL-6 stimulation.…”
Section: Discussionsupporting
confidence: 94%
“…This transcription factor, originally identified as a DNA-binding protein, is activated by many cytokines and growth factors and represents a key component in their signaling pathway [14]. Constitutive activation of STAT3 observed in many tumors including colon cancer [15] contributes to oncogenesis by modulating the expressions of a variety of genes involved in proliferation, invasion, metastasis, and angiogenesis [16,17]. In keeping with these observations, a large body of evidence indicates that blocking STAT3 activity suppresses tumor cell growth and induces tumor cell apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mRNA and protein levels of USP7 are markedly decreased in several types of cancer [28,29]. Moreover, dys-regulation of its expression and (or) activity contributes to oncogenic transformation and is crucial for cancer development [22,29]. However, the roles of USP7 in esophagus cancer cells remain poorly understood, although we found that USP7 also positively regulated p53 abundance upon metformin treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Besides, USP7 was shown to be involved in tumorigenesis [26,27]. For instance, mRNA and protein levels of USP7 are markedly decreased in several types of cancer [28,29]. Moreover, dys-regulation of its expression and (or) activity contributes to oncogenic transformation and is crucial for cancer development [22,29].…”
Section: Discussionmentioning
confidence: 99%